Interactions of Cetyltrimethylammonium Bromide with 1,3-Dioxolane in Water: A Study of Viscosity and Volumetric Properties - Sarangi, Dayananda; Samantaray, A.C.; Sahu, Rojalin; Nanda, Braja B. (Asian Journal of Chemistry, 2019)
Densities and viscosities of ternary mixtures containing cetyltrimethyl ammonium bromide (CTAB) in aqueous solution of 1,3-dioxolane have been measured at 5 K intervals from 298.15 to 313.15 K and at atmospheric pressure. The experimental results of viscosity and density have been analyzed by using Jones-Dole equation and Masson equation. The values of constants A and B of Jones-Dole equation have been interpreted in terms of solute-solute and solute-solvent interactions. The standard partial molar volume,Vf0 at infinite dilution were determined from Masson equations. The structure making/breaking capacity of solute is interpreted with the help of Helper equation. The positive value of Helper′s constant (∂2Vf0/∂T2)p and the negative value of dB/dT shows that CTAB in studied organic solvent predominantly acts as a structure-maker.